2019
DOI: 10.2478/jcbtp-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Leverage Ratio and its Potential For Enhancing the Effectiveness of Capital Regulation

Abstract: The article deals with the procyclical development of risk weights and hence the risk-weighted capital ratio. The leverage ratio should be included in the regulatory reform package (CRR2) as a (non-risk-weighted) prudential backstop. The article defines the complementary relationship of capital and leverage by describing their different responses to the cyclical development associated with the change in the quality of assets in the various phases of the financial cycle. The results of the panel regression on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Also, according to Basel III, the Counter-Cyclical Capital Buffer is built when there is strong economic growth to prevent pressure on capital during stress periods in a financial crisis (BIS 2023). Therefore, banks will be able to use capital reserve accumulated during the economic boom in the period of financial stress and use it to maintain smooth credit activity (Pfeifer and Pikhart 2019). Additionally, Liu and Molise (2019) concluded that the Basel III Counter-Cyclical Capital Buffer (CCB) effectively prevents fluctuations in housing and credit markets, and prevents bubbles.…”
Section: Evolution Of Basel Accordmentioning
confidence: 99%
“…Also, according to Basel III, the Counter-Cyclical Capital Buffer is built when there is strong economic growth to prevent pressure on capital during stress periods in a financial crisis (BIS 2023). Therefore, banks will be able to use capital reserve accumulated during the economic boom in the period of financial stress and use it to maintain smooth credit activity (Pfeifer and Pikhart 2019). Additionally, Liu and Molise (2019) concluded that the Basel III Counter-Cyclical Capital Buffer (CCB) effectively prevents fluctuations in housing and credit markets, and prevents bubbles.…”
Section: Evolution Of Basel Accordmentioning
confidence: 99%
“…The chapter describes options of regulatory changes to improve banks' ability to use the macroprudential buffers. 17 One approach to increase buffer usability would be to mirror all risk-weighted buffers with parallel LR-buffers (Pfeifer and Pikhart, 2019). This is currently the case for the G-SII buffer.…”
Section: The Options Of Regulatory Changes To Improving Buffer Usabilitymentioning
confidence: 99%
“…The leverage ratio requirement is very simple on its own (Pfeifer and Pikhart, 2019), but combined with the existing risk-weighted approach, it brings a new level of complexity to capital regulation. 1 The current regulation allows multiple use of capital to meet individual requirements, including capital buffers.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) interpret leverage as the use of assets and sources of funds from companies with fixed costs (fixed expenses), meaning that sources of funds originate from loans because they have an interest as a fixed burden to increase potential profits for shareholders. The leverage ratio measures how much the company is financed by debt (Pfeifer and Pikhart 2019). Leverage is a ratio explaining the relationship between a company's debt and capital or assets (Chen and Zhao 2007).…”
Section: Leveragementioning
confidence: 99%